Effect of Nb doping on epsilon negative behaviour of Sr2MnO4 - Nirala G.; Katheriya T.; Yadav D.; Pandey S.; Upadhyay S. (My University, 2025)
Solid-state ceramic route was used to synthesize certain Nb doped compounds of the system Sr2Mn1-xNbxO4 (x = 0.1, 0.2, 0.3, 0.4, 0.5) in air. Out of these, the x = 0.4, 0.5 compositions were found to consist of an impurity of Sr8Nb4O18, which elucidates a solubility limit of Nb in the Sr2MnO4. Permittivity and AC conductivity studies with respect to frequency and temperature exhibited negative permittivity in the entire range of the measurement (30–600 °C) for x = 0.1, 0.2 compositions, whereas in the case of x = 0.3, 0.4, and 0.5 compositions, the same behaviour was seen above 80, 180, and 230 °C, respectively. The plasmonic oscillations of charge carriers may be responsible for the negative permittivity behaviour, which is analysed by the Drude–Lorentz model. Compositional and temperature dependent sign of the permittivity of the system Sr2Mn1-xNbxO4 makes this system promising materials for switching action in the wide frequency range and temperature range. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.